DOES "IS" INNOVATION DIFFUSION CONTRIBUTE TO THE NON-FINANCIAL PERFORMANCE OF THE VILLAGE GOVERNMENT? - Zaitul Zaitul; Desi Ilona; Neva Novianti; Eugene Okyere-Kwakye (Assets: Jurnal Akuntansi dan Pendidikan, 2023)
ABSTRACTThis research paper analyzes the Influence of IS innovation diffusion on the performance/ outcome of the village government. Besides this paper also determines the role of organizational support and technological advantage in determining performance. Finally, this study researched these variables as moderating between IS innovation diffusion and implementation. The primary data was collected through a survey and analyzed using the smart-pls. The result shows that the technological advantage is significantly associated with the performance of the village government. This finding contributes to the technology organization environment.ABSTRAKPenelitian ini menganalisis pengaruh difusi inovasi SI terhadap kinerja pemerintah desa. Selain itu, penelitian ini juga menentukan peran dukungan organisasi dan keunggulan teknologi dalam menentukan kinerja. Terakhir, penelitian ini juga meneliti variabel-variabel tersebut sebagai variabel pemoderasi antara difusi inovasi SI dan kinerja. Data primer dikumpulkan melalui survei dan dianalisis menggunakan smart-pls. Hasil penelitian menunjukkan bahwa keunggulan teknologi berpengaruh secara signifikan dengan kinerja pemerintah desa. Temuan ini secara teoritis berkontribusi pada technology organization environment.